PENGARUH BUDAYA KERJA, GAYA KEPEMIMPINAN DAN KOMUNIKASI TERHADAP KINERJA KARYAWAN PADA DIVISI PRODUKSI PT FREEPORT ELECTRONICS INDONESIA - Adang, Adang Djatnika Effendi; Nabiela, Nabiela Rizki Alifa; Firda, Firda Septiany (Lobi, 2024)
Companies can identify their employees in various ways, such as how employees complete formal tasks and how they perform. Apart from that, factors such as work culture, leadership style and communication also play an important role in employee work processes. By paying attention to these aspects, companies will gain a deeper understanding of the contribution of employee performance. This research uses a descriptive verification method with a quantitative approach, with data collection through interviews and questionnaires. The research population consisted of 24 people. This research uses a saturated sampling method. The results of this research partially show that Work Culture does not have a significant effect on performance. Leadership style has a positive and significant effect as proven by tcount 2.303 and sig 0.032. Communication has a positive and significant effect as proven by tcount 3.210 and sig 0.004. Simultaneously work culture, leadership style and communication have a positive and significant effect which can be proven F calculated at 26.349 and sig 0.001